Evaluation of 17β-hydroxysteroid dehydrogenase activity using androgen receptor-mediated transactivation. Issue 196 (February 2020) - Yazawa, Takashi; Imamichi, Yoshitaka; Uwada, Junsuke; Sekiguchi, Toshio; Mikami, Daisuke; Kitano, Takeshi; Ida, Takanori; Sato, Takahiro; Nemoto, Takahiro; Nagata, Sayaka; Islam Khan, Md. Rafiqul; Takahashi, Satoru; et al.
Highlights: We established a cell-based method that evaluates enzymatic activity of HSD17B3. This system defined the enzymatic activities of various missense mutants of HSD17B3. The activities of HSD17B1and HSD17B5 could be evaluated using this system. Human HSD17B1 efficiently converts A4 into T under appropriate conditions. Abstract: 17β-Hydroxysteroid dehydrogenases (17β-HSDs) catalyze the reduction of 17-ketosteroids and the oxidation of 17β-hydroxysteroids to regulate the production of androgens and estrogens. Among them, 17β-HSD type 3 (HSD17B3) is expressed almost exclusively in testicular Leydig cells and contributes to development of male sexual characteristics by converting androstenedione (A4) to testosterone (T). Mutations of HSD17B3 genes cause a 46, XY disorder of sexual development (46, XY DSD) as a result of low T production. Therefore, the evaluation of 17β-HSD3 enzymatic activity is important for understanding and diagnosing this disorder. We adapted a method that easily evaluates enzymatic activity of 17β-HSD3 by quantifying the conversion from A4 to T using androgen receptor (AR)-mediated transactivation. HEK293 cells were transduced to express human HSD17B3, and incubated medium containing A4. Depending on the incubation time with HSD17B3-expressing cells, the culture media progressively increased luciferase activities in CV-1 cells, transfected with the AR expression vector and androgen-responsive reporter. Culture medium from HSD17B1 and HSD17B5-expressing cells also increased the luciferase activities. This system is also applicable to detect the conversion of 11-ketoandrostenedione to 11-ketotestosterone by HSD17B3. Establishment of HEK293 cells expressing various missense mutations in the HSD17B3 gene associated with 46, XY DSD revealed that this system is effective to evaluate the enzymatic activities of mutant proteins.